Pengaruh Pembelajaran Kooperatif Tipe Teams Game Tournament dengan Permainan Kapal Perang Terhadap Hasil Belajar Matematika - Lyna Hardiana (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
One method that can be used to increase students' confidence in mathematics is the teams game tournament (TGT) method. The purpose of this study was to determine the effect of the teams game tournament (TGT) learning model combined with the ship game on the mathematics learning outcomes of class VIII students on Cartesius coordinates. Sampling in this study using simple random sampling, the sample in this study involved 40 people, and was divided into two classes, namely the control class and the experimental class. The control class is a class that will receive conventional learning or the lecture method, while the experimental class is a class that will receive TGT learning. After getting the data in the form of pretest and posttest results, data analysis was carried out using the normality test, homogeneity test, t test and Mann-Whitney test to see the effect of the TGT learning method applied. Based on the normality and homogeneity test in posttest, it was found that the sample value was greater than 0.05 so it can be said that the sample was normally distributed and came from the same sample or population, but in pretest the sample is not normal. Based on the t test, it was found that the significance value of the sample was bigger than 0.05, so H0 was rejected and H1 was accepted or not rejected. This shows that the TGT learning method combined with war games affects the mathematics learning outcomes of class VIII students on the Cartesius coordinates material.